Eksplorasi intellectual capital Pemerintah Kota Semarang - Rahutama Atidira; Anjar Priyono (Jurnal Ekonomi Modernisasi, 2020)
This research aims to identify government activities that refer to Intellectual Capital resources at Pemerintah Kota Semarang (Local Government of Semarang City). Pemerintah Kota Semarang applies the Smart City concept to establish and enhance IC, therefore needs to identify IC components. The Public Sector IC concept in this research refers to the Spanish SICAP Project. The qualitative method with a single case holistic case study strategy is selected. Data is collected through interviews, observation, discussion, document checking, and the internet. Fifty-five IC activities have identified. IC forms reported through Penilaian Prestasi Kerja (Work Performance Assessment) and Local Government Financial Report in the form of intangible assets. All forms of intangible assets are computer software. The research found another component of Relational Capital is research collaboration. Research collaboration is managed by the Research and Development Field of Local Development Planning Agency. The Semarang City Government should be able to carry out an IC identification process so that it is in line with the explicit and implicit goals of a Smart Project. This process of identifying IC can provide information for valuation and henceforth can be a focus in the subject of managerial development within the Semarang City Government. Future research is hoped to be able to provide better IC deepening in each agency, agency, or office within the Semarang City Government.